Making Sense of Tantric Buddhism: History, Semiology, and Transgression in the Indian Traditions, by Christian K. Wedemeyer - DiValerio, David (Religions of South Asia, 2015)
Making Sense of Tantric Buddhism: History, Semiology, and Transgression in the Indian Traditions, by Christian K. Wedemeyer. New York: Columbia University Press, 2013. xx + 313 pp. £34.50. ISBN 0-231-16240-1 (hardback). £18.00. ISBN 0-231-16241-8 (paperback).